(untitled) (Research, Society and Development, 2022)
The composting process is an important practice for carcasses decomposition acceleration and inactivation of potentially pathogenic microorganisms present in the material to be decomposed. However, it is necessary to evaluate proper parameters of the process. Therefore, the present study aimed to evaluate the inactivation of pathogenic microorganisms in composters built in laboratory and pilot scale for decomposition of swine carcasses. For this purpose, composters were built on laboratory and pilot scale and known concentrations of pathogenic microorganisms were added (Escherichia coli e Salmonella Senftenberg). The reduction of these microorganisms was measured until there was non-detection of viable micro-organisms. The results indicated that the pilot-scale composting, due to their dimensions, reached the ideal process conditions and eliminated the pathogens more efficiently and quickly (in 7 days, when temperature was above 60ºC). Thus, this process is a promising alternative for the disposal of swine carcasses.